Sosiologi dalam Kajian Agama: (Kontribusi Kajian Keagamaan dalam Sosiologi Islam) - Asnawan Asnawan (FALASIFA : Jurnal Studi Keislaman, 2016)
In this paper wants to describe the sociological approach in the realm of religion and also questioned the functioning and development of integration-social integration or socio-religious movements. Therefore, it is important to understand religious phenomena that occur in the community because of attitudes and behavior is the application of a person's religious attitude. In normative in the verses of the Qur'an were revealed and studied a lot of it about muamalah or social problems. Â Keywords: Approach, sociology, Religion, Social Reality